Integrating Local Wisdom into Culture Schema–Based Reading to Advance Critical Literacy in EFL Higher Education - Faliyanti, Eva; Sinaga, Risma Margaretha; Siregar, Rabiyatul Adawiyah (Universitas Islam Negeri Raden Intan Lampung, 2026)
This study developed and evaluated a culture schema–based reading model that integrated local wisdom to strengthen critical literacy in an English as a Foreign Language (EFL) university context. The study addressed a persistent pedagogical gap: reading instruction often promotes textual comprehension, yet it rarely operationalizes students’ cultural background knowledge as an explicit resource for critical interpretation. A mixed-methods design was employed within a research and development framework using the ADDIE model, followed by a quasi-experimental pre-test–post-test control-group evaluation. Participants were 70 undergraduate students from the English Education Department at the University of Muhammadiyah Metro, assigned to an experimental group (n = 35) and a control group (n = 35). Quantitative data were collected through reading comprehension tests, a critical literacy rubric, and a culture schema activation questionnaire; qualitative data were obtained through classroom observation, reflective writing, and semi-structured interviews. The experimental group improved from a pre-test mean of 65.43 to a post-test mean of 82.71, whereas the control group increased from 64.86 to 71.29. ANCOVA confirmed a significant intervention effect, F(1,66) = 46.23, p < .001, partial η² = .41. The experimental group also outperformed the control group across all critical literacy dimensions, with the strongest advantage in cultural interpretation (d = 2.21). Schema activation was substantially higher in the experimental group (overall M = 4.21 vs. 2.84), and multiple regression showed that schema activation explained 61% of the variance in critical literacy performance. Qualitative findings further indicated cultural recognition, emotional resonance, cognitive bridging, and identity affirmation. Overall, the study shows that local-wisdom-based reading instruction can deepen comprehension, promote culturally grounded critique, and support more inclusive literacy pedagogy in higher education.